Controllable synthesis of hierarchical nickel hydroxide nanotubes for high performance supercapacitors. Issue 5 (3rd January 2018) - Wang, Yanbing; Shang, Bin; Lin, Feng; Chen, Yu; Ma, Ruguang; Peng, Bo; Deng, Ziwei
Abstract : Hierarchical Ni(OH)2 nanotubes synthesized by a self-sacrificial template method exhibit superior capacitance and stability as electrode materials for supercapacitors. Abstract : Hierarchical Ni(OH)2 nanotubes with ultrathin nanoflakes were successfully synthesized by a self-sacrificial template via a facile solvothermal method. The as-prepared Ni(OH)2 nanotubes exhibit a high specific capacitance of 1319 F g −1 at 3 A g −1, and retain 700 F g −1 (79.3% of the initial capacitance) at 5 A g −1 after 7000 cycles.